DETECTION OF ASPERGILLUS SPP. IN BIOLOGICAL SAMPLES BY REAL-TIME PCR - Bolehovska, Radka; Pliskova, Lenka; Buchta, Vladimir; Cerman, Jaroslav; Hamal, Petr (Biomedical papers, 2006)
Background: Recently, the proportion of invasive infections caused by the filamentous fungi of the Aspergillus genus are growing in immunocompromised persons particularly in transplant recipients and neutropenic patients. Unfortunately, laboratory diagnostics of invasive aspergillosis remains extremely difficult, mainly with regard to the sensitivity of the methods and to the correct interpretation of the results in particular.Aim: The aim of this work was to design a standard and reproducible Aspergillus DNA detection method and its validation. The second aim was to practically use this method for diagnosis of Aspergillus DNA in various samples in patients.Method: Real-time PCR with two hybridization probes. Amplification and on-line quantification was carried out on a LightCycler® 1.5 Instrument.Results: Specificity of the reaction was tested for A. fumigatus, A. flavus, A. niger and A. terreus, and its sensitivity was determined at 5 copies per ml. The reproducibility of the results was comparable to other methods, reported in the literature. Applicability of the real-time PCR was assessed for detection of Aspergillus DNA in 354 various clinical samples taken from 179 patients at risk of invasive aspergillosis over the period of 33 months. Of 354 samples 103 (29.10 %) taken from 65 patients (36.31 %) were evaluated as positive. Over one year, the percentage of positive samples was mostly about 30 % or less per month.Conclusions: Our results demonstrate the high sensitivity, specificity and reproducibility of this technique, and its usefulness for rapid laboratory diagnosis of invasive aspergillosis.
Keywords: DNA detection/Real-time PCR/Mycoses/Aspergillus/Laboratory diagnosis/ Invasive aspergillosis